Measuring and characterizing land use mix patterns of China's megacities: A case study of Shanghai. (27th August 2021) - Zheng, Hongyu; Zhuo, Yuefei; Xu, Zhongguo; Wu, Cifang; Huang, Jianhong; Fu, Qi
Abstract: Land use mix (LUM) is a key part of urban form, but the definitions and measures of LUM are debated. This study aims to reveal the spatial characteristics of LUM patterns by using a sample of 216 streets in Shanghai, a megacity of China. Firstly, a systematic quantitative framework for sustainable LUM is proposed. Then, an LUM degree index (LMDI) that integrates diversity, proximity and compatibility is developed to address the possible bias of a single dimension. Results suggest that areas with high diversity are not necessarily mixed, due to inaccessibility or negative externalities of land uses. Subsequently, spatial characteristics of LUM patterns that combine LMDI with dominant mix‐typologies are analyzed. Results show that residential & service‐dominated streets tend to exhibit higher mix, and are mainly distributed in the city center or the administrative core area. However, 44.4% of the streets with residential & industrial‐dominated or equally distributed mix have lower mix degree and are generally located in the outskirts. More optimized policies for urban periphery areas should be considered. LUM patterns present a detailed perspective to measure and depict the spatial features of LUM, and have the potential to assist urban planners in making decisions.